Knowledge-sharing Behaviour Through Leadership and Culture: The Moderating Role of Job Autonomy and Gender - Islam, Md. Asadul; Haque, A. K. M. Ahasanul; Rahman, Mahfuzur; Polay, Dieu Hack; Mas, Francesca (SAGE, 2025)
Abstract This study examines how participative leadership, digital leadership and digital organizational culture influence employees’ knowledgesharing behaviour and how these are moderated by job autonomy and gender in Malaysia. Responses from 412 employees were collected from various organizations in the tourism sector. The data analysis was conducted through PLS-SEM to test hypotheses. Participative leadership, digital leadership and digital organizational culture were found to have a significant influence on the knowledgesharing behaviour of employees. Our results also showed that job autonomy significantly moderates the relationship between digital organizational culture and knowledge-sharing behaviour. The research revealed that gender does not moderate the influence of participative leadership, digital leadership and digital organizational culture on knowledge-sharing behaviour. The study significantly contributes to strategically deploying technology in an increasingly digital business world. The study has important theoretical and practical implications, which are presented together with suggestions for further research.